Ultrasound-Assisted Solvent-Terminated Dispersive Liquid‒Liquid Microextraction for Determination of Atrazine and Simazine in Bovine Milk via GC‒MS - Fucci, Renata Gregorio; da Silva, Thais Cuartes; Felipe, Letícia Polli Glugoski; Cestaro, Beatriz Isabella; da Silva, Bruno José Gonçalves (Food analytical methods, 2025)
Atrazine (ATZ) and simazine (SMZ) are major herbicides in Brazilian cultivation areas, and through environmental persistence and bioaccumulation, these compounds can contaminate bovine milk and other products for human consumption. Thus, the present study aimed to develop an analytical method for the determination of ATZ and SMZ in bovine milk using ultrasound-assisted solvent-terminated dispersive liquid‒liquid microextraction (UA-ST-DLLME) and gas chromatography coupled with mass spectrometry (GC–MS). Protein precipitation was carried out by the addition of 0.8 g of NaCl and 5.0 mL of acetonitrile to 8.0-mL samples. The optimized UA-ST-DLLME method consisted of the addition of 1.8 mL of precipitation supernatant to 8.0 mL of 10.0% (m/V) NaCl solution, followed by sonication for 5 min, after which 1.75 mL of acetonitrile was added for the demulsifying step, which was completed after 5 min. Adequate linearity was observed for SMZ (5–350 µg/L) and ATZ (10–350 µg/L). Interday precision and accuracy ( n = 3) were ascertained for the lower concentration levels, 100 and 350 µg/L. The relative standard deviation (RSD) values were less than 20% for the lowest concentration levels and less than 15% for the remaining concentrations; however, for all the concentration levels evaluated in these assays, the accuracy values ranged from 95.2 to 109.9% for SMZ and from 100.8 to 113.2% for ATZ. Graphical Abstract